High-dose re-irradiation of intracranial lesions – Efficacy and safety including dosimetric analysis based on accumulated EQD2Gy dose calculation. (March 2021) - Stiefel, I.; Schröder, C.; Tanadini-Lang, S.; Pytko, I.; Vu, E.; Klement, R.J.; Guckenberger, M.; Andratschke, N.
Highlights: Re-irradiation of the brain is feasible with an encouraging overall survival. Treatment related toxicity was low within the reported dose range. EQD2 cumulative dose distributions were calculated using rigid registration. Dose-Response-Modelling with logistic regression showed a correlation of the D1cc brain with any grade of acute toxicity. Abstract: Introduction: The use of cranial re-irradiation is growing with improving overall survival and the advent of high-precision radiotherapy techniques. Still the value of re-irradiation needs careful evaluation regarding safety and efficacy. We analyzed dosimetric and clinical data of patients receiving cranial re-irradiation using EQD2 sum plans. Methods and material: We retrospectively analyzed the data of 76 patients who received repeated cranial radiotherapy from 02/2013 to 09/2016. 34 patients suffered from recurrent primary brain tumors, 42 from brain metastases. Dosimetric analysis was performed accumulating EQD2 dose distributions based on rigid image registration. Clinical and radiological data was collected at follow-ups including toxicity, local control and overall survival. Results: In total 76 patients had at least 2 courses of intracranial radiotherapy. The median accumulated prescription EQD2 dose was 96.5 Gy2 for all radiation courses combined. The median D(0.1 cc) of the brain for patients receiving more than 100 Gy2 was 114 Gy2 with a highest dose of 161.5 Gy2 . 74% of patients suffered from low grade (G1–G2) acute toxicity, only two high grade (>G3) toxicities were recorded. Median overall survival from the time of first re-irradiation was 57 weeks (range 4–186 weeks). The median time to local failure for patients with a primary brain tumor was not reached and 24 weeks (range 1–77 weeks) for patients with brain metastases. Conclusion: Repeated radiotherapy appears both safe and efficient in patients with recurrent primary or secondary brain tumors with doses to the brain up to 120 Gy2 EQD2, doses below 100 Gy2 for brainstem and doses below 75 Gy2 EQD2 to chiasm and optic nerves.